Hydrophobic and antifouling modification of graphene oxide with functionalized polynorbornene by surface-initiated ring-opening metathesis polymerization. (7th March 2022) - Lin, Xiaoxue; Shi, Jianjun; Shi, Zaifeng; Niwayama, Satomi
Abstract : Surface-initiated ring-opening metathesis polymerization (SI-ROMP), based on the design of hydrophobic and antifouling monomers, was employed for the synthesis of grafting-modified graphene oxide (GO). Abstract : Surface-initiated ring-opening metathesis polymerization (SI-ROMP), based on the design of hydrophobic and antifouling monomers, was employed for the synthesis of grafting-modified graphene oxide (GO). The activity of copolymerization was investigated with the use of fluorinated norbornenes (NBF n ) and polyethylene glycol-substituted norbornenes (Nb-PEG) as monomers in the presence of Grubbs 2nd generation catalyst in the solution conditions. These copolymerization conditions were applied to the modification of GO by SI-ROMP, and the polynorbornene-functionalized GO (GO-pNBFn -pNb-PEG) was obtained from the active catalyst sites on the GO surface. The results indicated that fine copolymerization activity was achieved under the molar ratio of 175 : 25 : 2 (NBF n : Nb-PEG : catalyst), whereas the activity of ROMP was decreased obviously with the increase of the Nb-PEG ratio and the side-chain length of the PEG groups. The modified GO retained the intercalated layer structure, and the growth of the polymers led to the decreased layer spacing. The grafting ratio could reach 37% by controlling the monomer concentration of 0.1 g mL −1 : 0.016 g mL −1 (NBF n : Nb-PEG) and polymerization time ( t 1 = 45 min and t 2 = 90 min) under the mild reaction conditions. The grafted polymer films improved the dispersibility of GO in organic solvents and the contact angle of GO-pNBF10 -pNb-PEG550 could reach 128°. The protein resistance of the modified GO had better anti-adsorption ability towards large molecular weight proteins.